Prognostic Values of E2F1/2 Transcriptional Expressions in Chromophobe Renal Cell Carcinoma Patients: Evidence from Bioinformatics Analysis - Hu D; Meng N; Lou X; Li Z; Teng Y; Tu B; Zou Y; Wang F (International Journal of General Medicine, 2021)
Dingtao Hu,1,* Nana Meng,2,* Xiaoqi Lou,1 Zhen Li,3 Ying Teng,3 Bizhi Tu,4 Yanfeng Zou,3 Fang Wang1 1Department of Oncology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China; 2Department of Quality Management Office, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China; 3Department of Epidemiology and Biostatistics, School of Public Health, Anhui Medical University, Hefei, Anhui, People’s Republic of China; 4Department of Orthopedics, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang WangDepartment of Oncology, The First Affiliated Hospital of Anhui Medical University, 218Jixi Road, Hefei, 230022, Anhui, People’s Republic of ChinaTel +86055162923615Fax +86055162923615Email wangfangahmu@163.comYanfeng ZouDepartment of Epidemiology and Biostatistics, School of Public Health, Anhui Medical University, No. 81, Meishan Road, Shushan District, Hefei, 230032, Anhui, People’s Republic of ChinaEmail zouyanfeng2015@163.comBackground: Numerous studies on the E2F transcription factors have led to increasing insights that E2Fs could be an important driver of the formation and progression of many human cancers. Little is known about the function of distinct E2Fs in chromophobe renal cell carcinoma (chRCC).Methods: We utilized the UALCAN, GEPIA, Cancer Genome Atlas (TCGA) database, cBioPortal, Metascape, STRING, Cytoscape, GeneMANIA, TIMER, TISIDB, GSCALite, and MEXPRESS databases to investigate the transcription level, genetic alteration, methylation, and biological function of E2Fs in chRCC patients, and its association with the occurrence, progress, prognosis, and immune cell infiltration in patients with chRCC.Results: We found that E2F1/2/4/7/8 were more expressed in chRCC tissues than in normal tissues, while the expression of E2F5/6 was lower in the former than in the latter, and the expression levels of E2F1/2/4/5/6//7/8 were also associated with the histological parameters of chRCC, including T-stage and N-stage. Higher expression of E2F1/2/7/8 was found to be significantly correlated with worse overall survival (OS) in chRCC patients. Cox regression and time-dependent ROC analysis further suggested that E2F1/2 could be the potential independent biomarkers for chRCC prognosis. Besides, a moderate mutation rate of E2Fs (34%) was noticed in chRCC, and the genetic mutations in E2Fs were associated with poor survival of chRCC patients. We noticed that the expression of E2Fs was statistically correlated with the immune cell infiltration in chRCC. Moreover, we also found that the expression of E2F1 was significantly correlated with tumor-infiltrating lymphocytes and immunomodulators, E2F7 expression was associated with MHC molecules, and the expression of E2F1/8 was correlated to their methylation levels.Conclusion: Our results provide novel insights for selecting the prognostic biomarkers for chRCC and suggest that E2F1/2 could act as potential prognostic biomarkers for the survival of chRCC patients. However, more in-depth experiments are required to identify the underlying mechanisms and verify the clinical value of E2F1/2 in the prognosis of chRCC.Keywords: chromophobe renal cell carcinoma, E2Fs, prognosis, UALCAN, GEPIA